Effect of pelvic floor muscle training On the urinary incontinence in women - Anahita Torkzadeh (Vesnu Publications, 2014)
Introduction: Urinary incontinence (UI) is a common problem among adults living in the community and it is more frequent in women. Its incidence increases with age, the number of pregnancy and body mass index (BMI). Conservative management is recommended as the first-line treatment. Physical therapies, particularly pelvic floor muscle exercise, are the mainstay of such conservative management. The purpose of this study was to summarize current literatures and describe trends in the use of pelvic floor muscle exercise in the management of urinary incontinence. Expression of these data will help physical therapists to engage in more effective treatment for this problem. Material and Methods: The researchers tried to gather and present the data using the articles published in the last two decades from 1990 to 2012. They were presented in English language on some main data bases like pub med, science direct and PEDro. Results: Ninety six papers were found and finally seventeen articles accepted to analyze based on keywords. The results showed that the use of pelvic floor exercise can be an effective method for treatment of urinary incontinence in women. Conclusion: In most studies, the effectiveness of pelvic floor exercise was evaluated only during the treatment time or immediately after it. Key words: Pelvic floor exercise, urinary incontinence in women, physical therapy